Quantum quench from a thermal initial state - Sotiriadis, S; Calabrese, P; Cardy, J (2009)
We consider a quantum quench in a system of free bosons, starting from a thermal initial state. As in the case where the system is initially in the ground state, any finite subsystem eventually reaches a stationary thermal state with a momentum-dependent effective temperature. We find that this can, in some cases, even be lower than the initial temperature. We also study lattice effects and discuss more general types of quenches. Copyright © 2009 EPLA.Association.